Experimental Study of Shadow Formation in Stellar Binoculars with a Combination of Objective and Ocular Lens Power - Sohibah, Siti; Sofa, Geitsha Kirana; Ayuwistira, Siti Aisyah; Hafizh, Rafi Maulana Abdul; Izzatulhaq, Azmi Aziz; Malik, Adam (EduFisika: Jurnal Pendidikan Fisika, 2025)
The purpose of this study was to determine how variations in lens power affect the clarity, sharpness, and magnification of the resulting image, and to find the most efficient combination of lens power to produce the best image. This study used a quantitative approach through direct experiments. The tools used in this study included an objective lens with +200 diopters, glasses with +100 and +50 diopters, a light source, an observer screen, a lens mount, and a distance meter. Data were collected through direct observation, magnification measurements, and image clarity assessment using a Likert scale. The results showed that eye lenses with lower magnification power (+50 D) produced more stable images, higher clarity scores (average 4.2/5), and lower focus stability (clarity score 3.4/5). However, lenses with higher magnification power (+100 D) produced greater magnification (up to 2×) but with lower clarity scores (average 4.2/5). This study provides empirical data on lens power variations in low-cost, classroom-based optical systems, a topic rarely studied in astronomy education research. This contrasts with most previous studies, which primarily focus on theoretical modeling or optimization of commercial telescopes. The novelty of this study is the use of lens power combinations in a simple, inexpensive, and reproducible educational experiment. This research enhances the quality of physics learning, particularly in students' understanding of optical concepts and their application of contextual practices in educational settings.